Efficacy of Cheiranthus Cheiri in the Treatment of Pericoronitis: A Double-blind, Randomized, Placebo-controlled Trial with Molecular Docking - Shubhamoy Ghosh; Aritra Roy Chowdhury; Sarbendu Paul; Avipsha Sarkar; Abhijit Rana; Mousumi Koley; Indrani Halder; Suman Chandra; Subhranil Saha (Dentistry and Medical Research)
Context: Pericoronitis is the soft-tissue inflammation surrounding the dental crown in a semi-erupted lower third molar. Patients with early-stage pericoronitis experience discomfort, redness, swelling, mucosal ulceration, and loss of function. There is a dearth of evidence-based, standardized treatments for pericoronitis. Aim: This trial attempted to explore the efficacy of Cheiranthus cheiri (CC) 30 cH against placebos in the treatment of pericoronitis by detecting group differences in pain on the visual analog scale (VAS) over 14 days of intervention. Subsequently, molecular docking of CC was performed to predict the binding affinity of ligands to receptor proteins. Materials and Methods: A 14-day, double-blind, randomized (2:1), placebo-controlled trial was undertaken at the Dental Outpatient Department of D. N. De Homoeopathic Medical College and Hospital. Sixty participants with pericoronitis were randomized to receive either CC 30 cH 12 doses (n = 40) or identical-looking placebos (n = 20). All the participants were instructed to gurgle with warm saline water 2–3 times a day. The primary outcome measure was the time (days) to resolution of pain, measured using 100 mm VASs, from baseline up to 14 days. Secondary outcome measures included time (days) to the resolution of swelling and trismus, measured up to 14 days; blood erythrocyte sedimentation rate, C-reactive protein, and total leukocyte count; and the Oral Health Impact Profile-14 questionnaire, measured at baseline and after 14 days. The intention-to-treat sample was analyzed; Kaplan–Meier analysis and Welch t-tests of unequal variances were run to detect group differences. The results of molecular docking were examined using Biovia’s Discovery Studio Visualizer. Results: Days to resolution of pain were significantly less in the treatment group than placebo (Mantel-Cox log-rank test: P =0.042). Similar significant results were also obtained in the resolution of swelling (P = 0.007) and trismus (P = 0.014) favoring CC 30cH against placebos; however, no differences were demonstrated in the other secondary outcomes. During molecular docking, all of the bioactive components of CC reacted with tumor necrosis factor-α, proving and verifying its anti-inflammatory potential. Conclusion: CC 30 cH produced significant treatment benefits by resolving pain, swelling, and trismus of pericoronitis earlier than placebos. Larger trials are warranted to substantiate the findings. Trial registration: CTRI/2023/04/051254; UTN: U1111-1289-9815.